Relationship between magnitude of phytoplankton blooms and rainfall in a hyper-eutrophic lagoon: A continuous monitoring approach. Issue 2 (30th November 2017) - Meng, Pei-Jie; Tew, Kwee Siong; Hsieh, Hung-Yen; Chen, Chung-Chi
Abstract: To evaluate the effect of rainfall intensity on phytoplankton blooms, a continuous monitoring system was deployed during 2015 in a hyper-eutrophic lagoon in Taiwan. Intensive rainfall occurs during the wet summer months, from May to September. Salinity in the lagoon was found to decrease with increasing intensity of rainfall. The magnitude of phytoplankton blooms also increased linearly with increasing rainfall intensity. The chlorophyll a concentration rose by an order of magnitude during the heaviest rainfall. Blooms may be fueled by nutrient enrichment caused by drainage or run-off water from surrounding areas that is channeled into the lagoon during rainfall events. During bloom periods, the rates of net primary production and ecosystem respiration were high. However, this ecosystem was autotrophic for most of the year. As extreme rainfall is predicted to increase, the results of this study imply that the frequency and magnitude of phytoplankton blooms may increase in the future. Highlights: To evaluate the effect of rainfall intensity on phytoplankton blooms Data recorded from a continuous monitoring system for a year in a hyper-eutrophic lagoon The magnitude of phytoplankton blooms increased linearly with increasing rainfall intensity. The chlorophyll a concentration rose by an order of magnitude during the heaviest rainfall During bloom periods, the rates of net primary production and ecosystem respiration were also high.